2008
DOI: 10.1002/hbm.20624
|View full text |Cite
|
Sign up to set email alerts
|

Movement gating of beta/gamma oscillations involved in the N30 somatosensory evoked potential

Abstract: Evoked potential modulation allows the study of dynamic brain processing. The mechanism of movement gating of the frontal N30 component of somatosensory evoked potentials (SEP) produced by the stimulation of the median nerve at wrist remains to be elucidated. At rest, a power enhancement and a significant phase-locking of the electroencephalographic (EEG) oscillation in the beta/gamma range (25-35 Hz) are related to the emergence of the N30. The latter was also perfectly identified in presence of pure phase-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 70 publications
(86 reference statements)
4
31
1
Order By: Relevance
“…Such additional proprioceptive information might refer to the coding of precise kinesthetic aspects of the observed movement and other body schema information, related to the preservation of body identity (Iacoboni et al, 1999). The similar localization in the motor cortex of the gamma phase locking, both at rest and during hand movement observation at the latency of the N30 component, reinforced previous findings, which suggested that gamma phase locking is the main mechanism underlying the N30 component, while gamma ERS might indicate a modulating role reflecting multimodal integration (Cebolla et al, 2009(Cebolla et al, , 2014.…”
Section: Cognitive Involvement Of the N30 Beta-gamma Oscillations Andsupporting
confidence: 76%
See 3 more Smart Citations
“…Such additional proprioceptive information might refer to the coding of precise kinesthetic aspects of the observed movement and other body schema information, related to the preservation of body identity (Iacoboni et al, 1999). The similar localization in the motor cortex of the gamma phase locking, both at rest and during hand movement observation at the latency of the N30 component, reinforced previous findings, which suggested that gamma phase locking is the main mechanism underlying the N30 component, while gamma ERS might indicate a modulating role reflecting multimodal integration (Cebolla et al, 2009(Cebolla et al, , 2014.…”
Section: Cognitive Involvement Of the N30 Beta-gamma Oscillations Andsupporting
confidence: 76%
“…While the earlier thalamic P14 and the parietal N20 remain stable, the N30 amplitude is highly sensitive to concurrent input from the periphery, such as superficial and deep muscle massage (Cheron and Borenstein, 1991) or centrally generated as motor execution, motor preparation and movement imagery (Rushton et al, 1981;Cheron andBorenstein, 1987, 1992;Rossini et al, 1999). Within the framework of the oscillatory approach, it has been demonstrated that when flexing the fingers of the stimulated hand, the phase consistency of the beta-gamma oscillations, identifiable when the stimulation was given at rest, was impinged (Cebolla et al, 2009). At precisely that point, the abolition of the N30 component was observed throughout its wide topographical distribution on the scalp.…”
Section: Beta-gamma Oscillations During Motor Gating Of the N30 Sepmentioning
confidence: 97%
See 2 more Smart Citations
“…Importantly, abnormal sensory gating has been N30 is gated during preparation, execution or imagination of movements to the same limb as MN stimulation (i.e. ipsilateral movements) [3][4][5][6][7][8][9][10][11][12][13][14]. In contrast, previous research has also shown that N30 peaks are enhanced during the execution of contralateral repetitive finger-to-thumb opposition movements [15] and during self-paced gripping [8].…”
Section: Introductionmentioning
confidence: 76%